Разработка методики определения функциональной асимметрии мозга у студентов вуза; Artium Magister; Т. 23, № 1 - Лизунков В. Г. Владислав Геннадьевич; Малушко Е. Ю. Елена Юрьевна; Трофимов А. В. Александр Валерьевич; Галицкий А. И. Антон Игоревич (2023, 2023)
Заглавие с экрана